The Effectivity of Interactive E-Module to Increase the Students' Visual-Spatial Intelligence on Ionic - Wahyu Ismi Zakiyah; Kusumawati Dwiningsih (Universitas Negeri Yogyakarta, 2022)
This study aims to test the effectiveness of interactive e-modules to train students' visual-spatial intelligence on ionic bonding material in terms of the students' pretest and posttest results. The research design applied in this study was a one-group pretest-posttest design. Where using the learning outcomes test sheet as the instrument used in this study and tested on 15 students in high school. Analysis of the data from the research results showed that the learning outcomes test that had been carried outreached an average N-gain of 0.81 with a high score criterion to measure the students' visual-spatial intelligence. The normality test used to determine whether the distribution of the data was normal or not showed results with a significance level of 0.836 for the pretest and 0.436 for the posttest, both of which had a significance level of 0.05. This matter prove if the analyzed data is normally distributed. And the last test is the paired sample t-Test which gets the sig value. (2-tailed) of 0.000 0.05, thus H1 accepted and H0 rejected so that there is a significant effect on giving treatment using interactive e-modules to train visual-spatial intelligence given to students.